Circulating microRNAs as biomarkers of reproductive status in the cow - Ioannidis, Jason (The University of Edinburgh, 2017)
Poor reproductive performance is a major challenge for the bovine dairy industry, with implications for profitability and animal welfare. Early pregnancy diagnosis and accurate oestrus detection can improve reproductive performance through efficient herd management. However currently available methods do not allow this. Circulating microRNAs (miRNAs) have been proposed as non-invasive biomarkers of reproductive status in humans. The hypothesis for this work was that differentially expressed miRNAs in plasma will be detectable during early pregnancy / oestrus, which may provide novel potential biomarkers. Using sequencing and PCR-based platforms I successfully identified and validated increases in miR-26a and the miR-26a / miR-205 ratio as early as Day 8 of pregnancy (max. 7.5-fold) in the plasma of pregnant compared to non-pregnant heifers. These miRNAs are known regulators of immunity, angiogenesis and metabolism, however their specific roles in early pregnancy remain to be investigated. I also identified small but significant increases in the levels of miR-125b, let-7f, miR-145 and miR-99a-5p at oestrus, when compared with the luteal phase of the cycle. These miRNAs have been previously shown to regulate the follicular to luteal transition in the bovine ovary. Finally, I provide a validated high-throughput resource which can help identify potential global biomarkers of tissue function, as shown for the liver-enriched miR-802 in the present results. The findings of this work may be useful in the development of diagnostic methods for early pregnancy and oestrus, and pave the way for the functional characterisation of these miRNAs in bovine reproduction.
Keywords: miRNA; bovine reproduction; pregnancy; cow; oestrus